INFLUENCE OF BUSINESS GROUPS, TAX PLANNING AND GOOD CORPORATE GOVERNANCE ON EARNING MANAGEMENT IS MODERATE BY OWNERSHIP OF CONTROLLING SHARES IN COMPANIES MERCHANT TO THE JAKARTA ISLAMIC INDEX 70 - Marnija; Holiawati; Endang Ruhiyat (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The aim of this research is to examine the influence of Business Groups, Tax Planning and Good Corporate Governance on Earning Management, moderated by Controlling Share Ownership. This type of research uses associative quantitative methods, which emphasize hypothesis testing through measuring research variables with numbers and analyzing data using statistical procedures. This research uses panel data. The objects of this research are companies that are members of the Jakarta Islamic Index 70 which are listed on the BEI for the 4 years 2020-2023. In this research, nonprobability sampling was used with a saturated sampling technique so that there were 70 samples and 280 observation data. This data analysis uses Panel Data Regression Test and Moderated Regression Analysis (MRA). The results of this research include that the Business Group and Tax Planning variables have no effect on Earning Management, while Good Corporate Governance has an effect on Earning Management. Meanwhile, the results of the Moderation test show that Controlling Share Ownership is able to moderate the relationship between Business Groups and Earning Management. Meanwhile, Controlling Share Ownership is unable to moderate the relationship between Tax Planning and Good Corporate Governance on Earning Management.